2022
DOI: 10.1029/2022jg006908
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Drivers and Pathways for Hydroelectric Reservoir Methane Emissions Using a New Mechanistic Model

Abstract: Hydroelectric power is the dominant source of renewable energy globally. In 2017, it comprised 13% of global electricity production in OECD (Organization for Economic Co-operation and Development) countries (International Energy Agency, 2018), and 2.5% of global energy production. While electricity from hydropower can replace electricity from carbon-intensive sources such as coal and gas, reservoirs also emit methane (CH 4 ) which could negate some of the carbon benefits of switching to hydropower. CH 4 is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 184 publications
(184 reference statements)
0
12
0
Order By: Relevance
“…17 As for agricultural ponds, reservoirs are also the focus of research to estimate their contributions to anthropogenic methane emissions more accurately. 30 Compared to reported statistics for established reservoirs in the 2024 national GHG inventory for the year 2022, agricultural ponds occupy 56% less surface area (173 vs 394 kha), yet they emit twice as much methane per area (0.238 vs 0.119 t CH 4 ha −1 ) and similar methane in total (41 vs 47 kt CH 4 year −1 ). However, emissions from established reservoirs have increased by 147% from 1990 to 2022 (from 19 to 47 kt CH 4 year −1 ), against the 58% increase (from 26 to 41 kt CH 4 year −1 ) from agricultural ponds.…”
Section: Discussionmentioning
confidence: 87%
“…17 As for agricultural ponds, reservoirs are also the focus of research to estimate their contributions to anthropogenic methane emissions more accurately. 30 Compared to reported statistics for established reservoirs in the 2024 national GHG inventory for the year 2022, agricultural ponds occupy 56% less surface area (173 vs 394 kha), yet they emit twice as much methane per area (0.238 vs 0.119 t CH 4 ha −1 ) and similar methane in total (41 vs 47 kt CH 4 year −1 ). However, emissions from established reservoirs have increased by 147% from 1990 to 2022 (from 19 to 47 kt CH 4 year −1 ), against the 58% increase (from 26 to 41 kt CH 4 year −1 ) from agricultural ponds.…”
Section: Discussionmentioning
confidence: 87%
“…Both degassing and ebullition fluxes are variable across different reservoirs. Median degassing flux was reported as one order magnitude lower than ebullition flux (Deemer et al., 2016); however, a modeling approach showed that for stratified hydropower reservoirs the degassing can be up to four times higher than ebullition (Delwiche et al., 2022). Temporally, considering monthly fluxes, the share of ebullition and degassing to the total CH 4 emissions was variable.…”
Section: Discussionmentioning
confidence: 99%
“…(2011)). CH 4 emissions from turbines and from anoxic hypolimnic water released from dams have been shown to be important emission paths (Delwiche et al., 2022; Harrison et al., 2021; Teodoru et al., 2015), but are still ignored in most global scale assessments. Less is known about the key drivers of river CH 4 flux.…”
Section: Inland Water Ch4 Budgetmentioning
confidence: 99%
“…Ebullition is usually reported to be the major emission path with flux rates nearly one order of magnitude higher than that of diffusion on average (Bastviken et al, 2011), though being less important in deeper parts of standing water bodies (>12 m depth in the study by Grinham et al (2011)). CH 4 emissions from turbines and from anoxic hypolimnic water released from dams have been shown to be important emission paths (Delwiche et al, 2022;Harrison et al, 2021;Teodoru et al, 2015), but are still ignored in most global scale assessments. Less is known about the key drivers of river CH 4 flux.…”
Section: Process Understandingmentioning
confidence: 99%